Albumin-to-neutrophil-lymphocyte ratio: a novel dual-pathway biomarker for diabetic retinopathy risk assessment - She, Chongyang; Tao, Yong; Yang, Shuo (Frontiers in Endocrinology, 2025)
BackgroundDiabetic retinopathy (DR) represents a leading cause of blindness globally, with conventional risk factors inadequately explaining disease occurrence and progression. The albumin-to-neutrophil-lymphocyte ratio (ANLR), a composite biomarker integrating nutritional and inflammatory status, has shown predictive value in various diabetic complications but its relationship with DR remains unexplored.MethodsThis cross-sectional study utilized National Health and Nutrition Examination Survey (NHANES) data from 1998–2020 cycles to investigate the association between ANLR and DR in diabetic patients with external validation in an independent study. ANLR was calculated as serum albumin divided by neutrophil-to-lymphocyte ratio. DR status was assessed through self-reporting in NHANES and ophthalmologic examination in the validation study. Survey-weighted generalized linear models were employed to evaluate associations, with participants stratified into quartiles based on ANLR values. Restricted cubic spline analysis examined nonlinear relationships, and subgroup analyses explored effect modification.ResultsA total of 6,279 diabetic participants were included in the NHANES analysis and 212 in the external validation study. After multivariable adjustment, higher ANLR quartiles demonstrated significantly reduced DR risk compared to Q1: Q2 (OR = 0.59, 95%CI: 0.38-0.91, P = 0.018), Q3 (OR = 0.73, 95%CI: 0.47-1.13, P = 0.164, non-significant), and Q4 (OR = 0.57, 95%CI: 0.36-0.90, P = 0.017). A significant dose-response relationship was observed (P for trend=0.044). Restricted cubic spline analysis revealed a nonlinear L-shaped association (P for nonlinearity=0.033), with rapid risk reduction at ANLR values <20 and plateau thereafter. The external validation study confirmed these findings with stronger associations (Q4 vs Q1: OR = 0.31, P = 0.010; P for trend=0.005) and demonstrated progressively lower ANLR levels across DR severity stages (no DR, NPDR, PDR; P for trend=0.017). Subgroup analyses identified significant interactions for sex, BMI, apolipoprotein B, and HDL-C, with stronger protective effects observed in females, individuals with higher BMI, and those with favorable lipid profiles.ConclusionANLR demonstrates a significant inverse association with DR risk and severity in diabetic patients, exhibiting a nonlinear dose-response relationship validated across independent populations. As an easily obtainable biomarker integrating inflammatory and nutritional status, ANLR may serve as a valuable tool for DR risk stratification and early identification of high-risk patients, potentially guiding personalized prevention strategies.